A CoS2-C / CNT composite material and its preparation method and application

By using CoS2-C/CNT composite material as the transduction layer, the problem of poor cyclic stability of single metal CoS2 in electrochemical reactions is solved, and an electrochemical material with high cyclic stability and capacitance performance can be achieved, which can effectively detect potassium, sodium, calcium, and magnesium ions.

CN118954618BActive Publication Date: 2025-04-18HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411056015.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-04-18
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

The cycling stability of a single transition metal sulfide during the electrochemical reaction is poor, volume expansion leads to the breaking of the electrode, and the reaction intermediate is easily dissolved, reducing the stability and service life of the material.

Method used

CoS2-C/CNT composite material is used as the transduction layer, and the Co-C/CNT composite material is formed by calcining the ZIF-67 precursor in a carbonization atmosphere and vulcanizing it in nitrogen or argon to form a composite material in which CoS2 nanoparticles interwoven connected by carbon nanotubes are embedded in a porous carbon matrix.

Benefits of technology

The cyclic stability and capacitance performance of the material are significantly improved, and the detection of potassium, sodium, calcium and magnesium ions is achieved, with the detection limits reaching 10-5.5M, 10-5.1M, 10-7.2M and 10-6.3M.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954618B_ABST
    Figure CN118954618B_ABST
Patent Text Reader

Abstract

The present invention discloses a CoS2-C / CNT composite material and its preparation method and application, and its preparation method comprises the following steps: a cobalt salt solution is slowly poured into an organic ligand solution, and a ZIF-67 precursor is obtained by stirring the reaction; in a carbonizing atmosphere, it is calcined and carbonized, the carbide is ground and mixed with sulfur powder, and then calcined and vulcanized under nitrogen or argon to obtain a CoS2-C / CNT composite material; the carbonizing atmosphere is a nitrogen atmosphere or a mixed atmosphere of argon and hydrogen. The present invention uses ZIF-67 as a precursor, and sequentially obtains a composite material in which CoS2 nanoparticles are uniformly embedded in a porous carbon matrix and are interwoven and connected by carbon nanotubes without additionally adding carbon nanotubes through carbonization and vulcanization. Thereby promoting electron transfer, ensuring high electronic conductivity, and significantly improving the cyclic stability of the material and the reversibility of the conversion reaction, effectively maintaining the excellent capacitance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical analysis sensor materials and relates to a CoS2-C / CNT composite material and a preparation method and application thereof. Background Art

[0002] All-solid-state ion-selective electrodes are widely used in environmental monitoring, human body fluid detection, biomedical analysis and other fields due to their advantages of high sensitivity, good selectivity, fast response speed and easy miniaturization. However, the potential potential drift problem affects the accuracy of the measurement results, restricting the practical application of all-solid-state ion-selective electrodes. An important component of the all-solid-state ion-selective electrode is the transduction layer, which can stabilize the phase interface potential between the ion-selective membrane and the conductive matrix, and can solve the potential drift problem of the ion-selective electrode. And the transduction layer is a mutual converter of ion-electron signals on the interface, and the interface capacitance brought by it is negatively correlated with the electrode potential drift value. That is, the transduction layer with excellent capacitance can ensure an interface that is not easily polarized and a sufficiently high current exchange density, thereby improving the stability of the electrode during potential response. Therefore, designing a transduction layer with excellent capacitance has important guiding significance for improving the stability of all-solid-state ion-selective electrodes.

[0003] As a member of transition metal sulfides, CoS2 has excellent conductivity and theoretical specific capacity. However, single transition metal sulfides break the electrode due to volume expansion during the electrochemical reaction, resulting in poor cycle stability; at the same time, the polysulfide intermediates in the reaction process are easily dissolved in the electrolyte solution, resulting in the attenuation of the material's specific capacity, which greatly reduces the intrinsic stability and service life of the material.

[0004] Using a porous carbon matrix with high porosity and high specific surface area as a carrier to fix metal sulfide, the intermediate of sulfide in the reaction process can be captured to avoid the dissolution of nanoparticles; at the same time, the carbon matrix carrier can also reduce the metal sulfide particles to the nanoscale, significantly reducing the mechanical stress associated with the conversion reaction, thereby alleviating the dissolution and fragmentation problems of sulfide in the reaction process, and significantly improving the cyclic stability of metal sulfide and the reversibility of the conversion reaction. In addition, interweaving and connecting individual materials through carbon nanotubes can provide a continuous and rapid transmission path for electrons, improve conductivity, and show excellent capacitance performance. Therefore, the present invention constructs a CoS2-C / CNT composite material interwoven and connected by carbon nanotubes with excellent conductivity, large capacitance, and high cyclic stability, and constructs an all-solid-state ion-selective electrode based on it as a transduction layer, realizing the detection of potassium, sodium, calcium, and magnesium ions. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a CoS2-C / CNT composite material and its preparation method and application, which solves the problem of poor cyclic stability of monometallic CoS2 and realizes the detection of potassium, sodium, calcium and magnesium ions.

[0006] The specific technical solutions of the present invention are as follows:

[0007] A method for preparing a CoS2-C / CNT composite material comprises the following steps:

[0008] S11, slowly pouring the cobalt salt solution into the organic ligand solution, stirring and reacting to obtain a ZIF-67 precursor;

[0009] S12, calcining and carbonizing the ZIF-67 precursor in a carbonizing atmosphere to obtain carbide Co-C / CNT; the carbonizing atmosphere is a nitrogen atmosphere or a mixed atmosphere of argon and hydrogen, and the volume content of hydrogen in the mixed gas is 5%;

[0010] S13, grinding and mixing the carbide Co-C / CNT and sulfur powder, and then calcining and sulfurizing them under nitrogen or argon to obtain a CoS2-C / CNT composite material.

[0011] In a further embodiment, the molar ratio of the cobalt salt to the organic ligand is 1:2-4;

[0012] The cobalt salt is at least one of cobalt nitrate hexahydrate (CoCl2·6H2O) and cobalt sulfate heptahydrate (CoSO4·7H2O); the organic ligand is at least one of 2-methylimidazole and 2-nitroimidazole.

[0013] The cobalt salt solution in the present application refers to the solution obtained by dissolving cobalt salt in methanol, and its concentration may preferably be 0.1 mol / L; the organic ligand solution refers to the solution obtained by dissolving organic ligand in methanol, and its concentration may preferably be 1.2 mol / L.

[0014] In a further embodiment, the stirring reaction in step S11 refers to stirring for 20-40 minutes first, and then standing at 20-25° C. for 36-60 hours; after the stirring reaction is completed, the product is centrifuged and washed with methanol, and vacuum dried to obtain a ZIF-67 precursor.

[0015] In a further embodiment, in step S12, the ZIF-67 precursor is calcined and carbonized by heating the temperature to 700-900° C. at a heating rate of 2-10° C. / min and calcining for 2-10 hours.

[0016] In a further embodiment, in step S13, the mass ratio of carbide Co-C / CNT to sulfur powder is 1:1-1.5.

[0017] In a further embodiment, the calcination and sulfurization in step S13 is performed by heating the temperature to 300-600° C. at a heating rate of 2-10° C. / min and calcining for 2-6 hours.

[0018] The second object of the present invention is to provide a CoS2-C / CNT composite material prepared by the above preparation method.

[0019] The third object of the present invention is to provide an application of the CoS2-C / CNT composite material as a transduction layer material in an all-solid-state ion selective electrode.

[0020] In a further embodiment, the method for preparing the all-solid-state ion selective electrode comprises the following steps:

[0021] S21, ultrasonically dispersing the CoS2-C / CNT composite material in ethanol or deionized water to obtain a dispersion;

[0022] S22, dripping the dispersion onto the electrode surface and drying;

[0023] S23, drop-coating the ion selective membrane solution on the top of the electrode treated in step S22, and drying, thereby obtaining a fully solid-state ion selective electrode.

[0024] In a further embodiment, the electrode is a glassy carbon electrode or a screen-printed electrode;

[0025] The ion selective membrane solution is a potassium, sodium, calcium or magnesium ion membrane solution;

[0026] The all-solid-state ion selective electrode is used for detecting potassium, sodium, calcium or magnesium ions.

[0027] The present invention is to carbonize in a carbonizing atmosphere (nitrogen atmosphere or a mixed atmosphere of argon and hydrogen) at a temperature of 700-900°C, and ZIF-67 as a precursor will be decomposed into Co 2+ , carbon materials, etc., among which Co 2+ Oxidation-reduction reaction occurs to generate Co particles. And the generated Co particles have catalytic activity. At high temperatures, the carbon atoms in the carbon material are rearranged under the catalytic action of the Co particles to form carbon nanotubes with tubular structure. Therefore, the present invention uses ZIF-67 as a precursor, and after carbonization, generates a carbide Co-C / CNT containing carbon and carbon nanotubes simultaneously without the additional addition of carbon nanotubes. Then it is sulfurized again to obtain the CoS2 nanoparticles interwoven and connected by carbon nanotubes and embedded in a porous carbon matrix composite material.

[0028] The CoS2-C / CNT composite material prepared by the present invention contains both carbon nanotubes and porous carbon matrix, and the interwoven carbon nanotubes and porous carbon matrix can effectively promote electron transfer and ensure high electronic conductivity; at the same time, the large amount of CoS2 particles also improve the reaction activity and provide more active sites. In addition, the interwoven carbon nanotubes and porous carbon matrix effectively avoid the dissolution of sulfide particles during the reaction process, significantly improve the cyclic stability of the material and the reversibility of the conversion reaction, thereby effectively maintaining excellent capacitance. That is, the CoS2-C / CNT composite material prepared by the present invention can greatly improve the cyclic stability of the composite material (capacitance retention rate after 1000 cycles of cyclic voltammetry curve test is 99.16%) and the material capacitance (maximum reaching 610μF).

[0029] The carbonization atmosphere and temperature in the present invention are key conditions for catalytically generating carbon nanotubes, and the amount of carbon nanotubes can be controlled by controlling the carbonization time. Experiments have shown that as the carbonization time increases, the amount of carbon nanotubes gradually decreases, while the amount of cobalt particles gradually increases. The Co-C / CNT-6h obtained by carbonization for 6h contains both appropriate amounts of carbon nanotubes and cobalt particles. The metal sulfide particles are embedded in the carbon matrix and entangled together by CNTs when the carbonization time increases.

[0030] The present invention regulates the amount of CoS2 and carbon nanotubes in the CoS2-C / CNT composite material by controlling the calcination carbonization time and sulfurization temperature of the ZIF-67 precursor. The composite material is recorded as CoS2-C / CNT-xh-y (where x is the calcination carbonization time and y is the calcination sulfurization temperature); wherein the CoS2-C / CNT-6h-500 obtained by calcination carbonization for 6h and calcination sulfurization at 500°C has a very large capacitance (610μV) and excellent cycle stability (capacitance retention rate of 99.16% after 1000 cycles of cyclic voltammetry curve test).

[0031] The present invention uses CoS2-C / CNT composite material as the transduction layer to prepare an all-solid-state ion-selective electrode, which can detect potassium, sodium, calcium or magnesium ions with a detection limit of K + :10 -5.5 M, Na + :10 -5.1 M, Ca 2+ :10 -7.2 M, Mg 2+ :10 -6.3 M. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1In the middle, ac is the scanning electron microscope images of carbides Co-C / CNT-2h, Co-C / CNT-6h, and Co-C / CNT-10h; df is the scanning electron microscope images of CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500, and CoS2-C / CNT-10h-500 composite materials;

[0033] Figure 2 Scanning electron microscope images of CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400, and CoS2-C / CNT-6h-600 composite materials;

[0034] Figure 3 Transmission electron microscopy images of carbide Co-C / CNT-6h and CoS2-C / CNT-6h-500 composites;

[0035] Figure 4 is the X-ray diffraction pattern of CoS2-C / CNT composite material;

[0036] Figure 5 N2 adsorption-desorption curve of CoS2-C / CNT composite material;

[0037] Figure 6 Cobalt scan and sulfur scan of X-ray photoelectron spectrum of CoS2-C / CNT-6h-500 composite material;

[0038] Figure 7 In the figure, ac is the cyclic voltammetry curves of different materials, d is the corresponding integral area diagram, and ef is the cyclic voltammetry curves of CoS2 material and CoS2-C / CNT-6h-500 composite material with continuous scanning of 1000 cycles respectively;

[0039] Figure 8 Cyclic voltammetry curves of CoS2-C / CNT-6h-500 materials with different loading amounts on the electrode surface and the corresponding integrated area diagram;

[0040] Fig. 9 The potential response diagram and calibration curve diagram of the all-solid-state ion selective electrode based on CoS2-C / CNT-6h-500. DETAILED DESCRIPTION

[0041] The present invention will be further explained below in conjunction with the embodiments and drawings, but the present invention is not limited thereto.

[0042] The reagents and materials used in the following examples are all commercially available products, and all reagents can be used directly without further purification.

[0043] Embodiment 1:

[0044] Preparation of CoS2-C / CNT composites:

[0045] S11. First, 30 mmol of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 0.3 L of methanol to form solution 1; 120 mmol of 2-methylimidazole was dissolved in 0.1 L of methanol to form solution 2.

[0046] S12. While stirring, slowly pour solution 1 into solution 2 and stir for 30 min, then let the mixture stand at 22°C for 48 h. After the stirring reaction, collect the purple precipitate by centrifugation and washing with methanol for 5 times, and vacuum dry at 60°C to obtain a ZIF-67 precursor.

[0047] S13, put the ZIF-67 precursor powder into a magnetic boat, then put it into a tube furnace, and heat it to 900℃ at a heating rate of 5℃ / min in a N2 atmosphere, and calcine and carbonize it for 2h, 6h, and 10h respectively. After cooling to room temperature, collect the black powder and record it as Co-C / CNT-xh (x is the carbonization time), such as carbides Co-C / CNT-2h, Co-C / CNT-6h, and Co-C / CNT-10h.

[0048] S14. Mix the above-mentioned black Co-C / CNT-xh powder and sulfur powder in a mass ratio of 1:1.25 and grind them evenly, then put them into a magnetic boat, and then place them in a tubular furnace. In a N2 atmosphere, heat them to 500°C at a heating rate of 5°C / min and calcine and vulcanize them for 2 hours. After naturally cooling to room temperature, collect the black product and record it as CoS2-C / CNT-xh-y (x is the carbonization time, y is the vulcanization temperature) composite material. Specifically, CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500, CoS2-C / CNT-10h-500 composite materials;

[0049] In addition, the carbide Co-C / CNT-6h was calcined and sulfurized at different sulfurization temperatures (200, 300, 400, 500, 600°C) for 2h to obtain CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400, and CoS2-C / CNT-6h-600 composite materials.

[0050] Test Example 1:

[0051] Figure 1Ac in the figure are scanning electron microscope images of the carbides Co-C / CNT-2h, Co-C / CNT-6h, and Co-C / CNT-10h obtained in step S13 of Example 1. It can be seen from the figure that there are a large number of carbon nanotubes in the Co-C / CNT-2h obtained by carbonization for 2h, while the number of cobalt particles is relatively small; there are both appropriate amounts of carbon nanotubes and cobalt particles in the Co-C / CNT-6h obtained by carbonization for 6h; when the carbonization time reaches 10, the number of carbon nanotubes decreases significantly, and the number of cobalt particles increases significantly. That is, as the carbonization time increases, the number of carbon nanotubes gradually decreases, and the number of cobalt particles gradually increases.

[0052] Figure 1 df in the figure are scanning electron microscope images of the composite materials of CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500 and CoS2-C / CNT-10h-500 obtained after each carbide was sulfurized at 500℃ for 2h in step S14. It can be seen from the figure that the overall morphology of the composite material after sulfurization has not changed significantly, but the surface has become rougher.

[0053] Co-C / CNT-6h with appropriate amount of carbon nanotubes and cobalt particles was selected as the target carbide, and then different sulfurization temperatures were optimized. That is, Co-C / CNT-6h was calcined and sulfurized at 200, 300, 400, and 600℃ for 2h to obtain CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400, and CoS2-C / CNT-6h-600 composite materials. Figure 2 Figures ad in the figure show scanning electron microscope images of the composite material. Figure 2 It can be seen that different vulcanization temperatures do not significantly change the morphology of the material.

[0054] Test Example 2:

[0055] Figure 3 In the figure, ab and cd are transmission electron micrographs of the carbide Co-C / CNT-6h and CoS2-C / CNT-6h-500 composite materials prepared in Example 1, respectively. Figure 1 From the SEM images, it can be observed that the CoS2-C / CNT-6h-500 composite material has a uniform micro-polyhedral shape, retaining the original shape of the ZIF-67 precursor and the Co-C / CNT-6h intermediate. The CoS2 particles are embedded in the carbon matrix, and the micro-polyhedral particles are entangled by CNTs, with a relatively rough surface.

[0056] Test Example 3:

[0057] Figure 4a is the X-ray diffraction pattern of the CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500, and CoS2-C / CNT-10h-500 composite materials prepared in Example 1. Figure 4 It can be seen that the composite materials obtained after different carbonization times and sulfidation at 500℃ for 2h all show the diffraction peaks of the XRD spectrum standard card of CoS2 (JCPDS#89-1492) and the XRD spectrum standard card of graphite (JCPDS#75-1621), indicating that CoS2-C / CNT composite materials are generated. However, the different carbonization times do not significantly change the diffraction peaks.

[0058] Figure 4 b is the X-ray diffraction patterns of the above-mentioned carbide Co-C / CNT-6h carbonized for 6h, and the composite materials of CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400, CoS2-C / CNT-6h-500, and CoS2-C / CNT-6h-600 obtained by calcining and sulfurizing for 2h at different sulfurization temperatures (200, 300, 400, 500, and 600°C). As can be seen from the figure, with the increase of sulfurization temperature, the intensity of the overall diffraction peak of the composite material gradually increases, indicating that the crystallinity gradually increases. When the sulfurization temperature is 200°C, there is no characteristic diffraction peak of the XRD spectrum standard card of CoS2 (JCPDS#89-1492), which is due to the incomplete reaction caused by the low sulfurization temperature. Therefore, the vulcanization temperature in this application is 300-600°C.

[0059] Test example 4:

[0060] The BET (Brunauer-Emmett-Teller) method was used to carry out N2 adsorption-desorption experiments, that is, the specific surface area tests were carried out on the CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500, CoS2-C / CNT-10h-500, CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400 and CoS2-C / CNT-6h-600 composite materials prepared in Example 1.

[0061] from Figure 5 It can be seen that when the vulcanization temperature is the same, as the carbonization time increases, the specific surface area gradually decreases (such as Figure 5 ac), it may be because the increase of carbonization time makes the number of carbon nanotubes gradually decrease. When the carbonization time is the same, as the sulfurization temperature increases, the specific surface area gradually increases (such as Figure 5This is because as the sulfurization temperature increases, the volatilization of free sulfur and the loss of carbon and heteroatoms in the carbon skeleton lead to the exposure of nanopores, thereby increasing the specific surface area of ​​the material.

[0062] Test Example 5:

[0063] like Figure 6 As shown, a and b are the cobalt scan and sulfur scan of the X-ray photoelectron spectrum (XPS) of CoS2-C / CNT-6h-500, respectively. In the high-resolution XPS spectrum of Co, the characteristic peaks of 778.9 and 794.1 eV correspond to Co-S bonds, and the characteristic peaks of 780.5 and 796.9 eV correspond to Co-O bonds, indicating the formation of CoS2 crystals. In the high-resolution XPS spectrum of S, the two characteristic peaks of 163.0 and 164.2 eV correspond to Co-S bonds, and the peak of 161.8 eV corresponds to the SC bond. The presence of the CS bond indicates that sulfur atoms are doped in the carbon matrix, which provides defect sites and good conductivity for the carbon matrix.

[0064] Test Example 6:

[0065] The capacitance of each material is measured using cyclic voltammetry. The test results are as follows: Figure 7 As shown, the specific test process is as follows:

[0066] A glassy carbon electrode with a diameter of 3 mm was polished on deerskin with 0.3 μm and 0.05 μm alumina powder, respectively, and then ultrasonically cleaned with a nitric acid aqueous solution with a volume ratio of 1:5 (nitric acid: water), ethanol and deionized water in sequence for use.

[0067] 28 mg of CoS2 particles, CoS2-C / CNT-2h-500, CoS2-C / CNT-6h-500, CoS2-C / CNT-10h-500, CoS2-C / CNT-6h-200, CoS2-C / CNT-6h-300, CoS2-C / CNT-6h-400 and CoS2-C / CNT-6h-600 composites were ultrasonically dispersed evenly in 1 mL of deionized water, and then 10 μL of the dispersion was dropped on the pretreated glassy carbon electrode surface using a pipette and dried in a fume hood.

[0068] A three-electrode system was used, with a glassy carbon electrode (GCE, 3 mm in diameter) as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl (3 mol / L KCl) as the reference electrode. The electrochemical properties of different electrodes were tested by cyclic voltammetry (CV) in 0.1 M KCl solution using a CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., China).

[0069] Figure 7In the figure, ac are the cyclic voltammetry curves of the above materials, Figure 7 d in the figure is the corresponding integral area diagram. It can be seen from the figure that at the same sulfurization temperature, the longer the carbonization time, the larger the current area. Figure 7 As shown in a, the current area of ​​CoS2-C / CNT-10h-500 is the largest; while the CoS2-C / CNT-6h-500 prepared at a sulfurization temperature of 500°C for the same carbonization time of 6h has the largest current area, indicating that it has the largest capacitance (e.g. Figure 7 As shown in b). Figure 7 As shown in c, the CoS2-C / CNT-6h-500 composite material has higher capacitance than CoS2.

[0070] At the same time, the integral area graph shows that the integral area of ​​CoS2-C / CNT-6h-500 is about 90 times that of CoS2 particles. This is because the presence of a large number of carbon nanotubes and CoS2 particles embedded in the carbon matrix increases the material capacitance, and the interwoven carbon nanotubes and porous carbon matrix can effectively promote electron transfer and ensure high electronic conductivity; at the same time, the presence of a large number of CoS2 particles also increases the reaction activity and provides more active sites.

[0071] The cyclic voltammetry curve of 1000 consecutive scans ( Figure 7 Figure ef) shows that after 1000 cycles, the capacitance retention rate of CoS2 particles is only 77.78%, while the capacitance retention rate of CoS2-C / CNT-6h-500 is as high as 99.16%. This is because the monometallic CoS2 particles will undergo volume expansion and dissolution of sulfide intermediates during the reaction, resulting in poor cycle stability and rapid reduction in specific capacity. The interwoven carbon nanotubes and porous carbon matrix in the CoS2-C / CNT-6h-500 composite material effectively avoid the dissolution of sulfide particles during the reaction, significantly improve the material's cycle stability and reversibility of the conversion reaction, thereby effectively maintaining excellent capacitance.

[0072] Test Example 7:

[0073] Taking CoS2-C / CNT-6h-500 with the largest capacitance as the target material, an optimization test for the optimal mass loading was carried out. The specific process is as follows:

[0074] Weigh 4-36 mg of CoS2-C / CNT-6h-500 composite material and disperse it in 1 mL of deionized water and ultrasonicate for 30 minutes to prepare CoS2-C / CNT-6h-500 dispersions with different concentrations of 4, 8, 12, 16, 20, 24, 28, 32, and 36 mg / mL;

[0075] Then, 10 μL of each of the above CoS2-C / CNT-6h-500 dispersions was dripped onto the surface of the glassy carbon electrode (the pretreatment of the glassy carbon electrode was the same as in Experimental Example 5), and GC / CoS2-C / CNT-6h-500 electrodes with mass loadings of 0.04, 0.08, 0.12, 0.16, 0.20, 0.24, 0.28, 0.32, and 0.36 mg were prepared;

[0076] Then the above electrodes were subjected to cyclic voltammetry test and the corresponding current integrated area-mass loading diagram was plotted, as shown in Figure 8 As shown in ab. It can be seen from the figure that when the mass loading of CoS2-C / CNT-6h-500 is 0.28 mg, the integrated area of ​​the current is the largest, indicating that 0.28 mg is the optimal mass loading of the CoS2-C / CNT-6h-500 composite material. Therefore, this loading is selected for the construction of the all-solid-state ion selective electrode in the following application example.

[0077] Application examples:

[0078] The CoS2-C / CNT-6h-500 composite material prepared in Example 1 was used as a transduction layer to prepare an all-solid-state ion selective electrode, as follows:

[0079] S21, ultrasonically dispersing the CoS2-C / CNT-6h-500 composite material in water to obtain a dispersion with a concentration of 28 mg / mL;

[0080] S22, use a pipette to take 10 μL of the dispersion and drop it onto the surface of the glassy carbon electrode, and place it in a fume hood to dry;

[0081] S23. Apply 100 μL of the ion selective membrane solution in batches of 10 μL each time on the top of the electrode treated in step S22, and place it in a fume hood to dry, thereby obtaining a fully solid-state ion selective electrode.

[0082] Preparation of the glassy carbon electrode: A glassy carbon electrode with a diameter of 3 mm was polished on deerskin with 0.3 μm and 0.05 μm alumina powder, respectively, and then ultrasonically cleaned with nitric acid aqueous solution, ethanol and deionized water in a volume ratio of 1:5 in sequence for use.

[0083] The preparation of ion selective membrane solution is known, and the present invention is exemplified as follows:

[0084] Preparation of potassium ion selective membrane solution: 1% wt valinomycin, 0.5% wt potassium tetrakis(4-chlorophenyl)borate (KTpClPB), 62.5% wt di-n-octyl sebacate (DOS), 18% wt polyvinyl chloride (PVC) and 18% wt polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene were mixed (a total of 200 mg), and then 2 mL of tetrahydrofuran (THF) was added and stirred at room temperature until a transparent solution was obtained.

[0085] Preparation of sodium ion selective membrane solution: 1% wt sodium ion carrier X, 0.4% wt sodium tetrakis[3,5-di(trifluoromethyl)phenyl]borate (NaTFPB), 65.7% wt di-n-octyl sebacate (DOS), 16.45% wt polyvinyl chloride (PVC) and 16.45% wt polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene were mixed (a total of 250 mg), and then 2.5 mL of tetrahydrofuran (THF) was added and stirred at room temperature until a transparent solution was obtained.

[0086] Preparation of calcium ion selective membrane solution: 1.3% wt calcium ion carrier II (ETH 129), 0.6% wt sodium tetrakis[3,5-di(trifluoromethyl)phenyl]borate (NaTFPB), 65.4% wt 2-nitrophenyl octyl ether (o-NPOE), 16.35% wt polyvinyl chloride (PVC) and 16.35% wt polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene were mixed (360 mg in total), and then 3 mL of tetrahydrofuran (THF) was added and stirred at room temperature to obtain a transparent solution.

[0087] Preparation of magnesium ion selective membrane solution: 1.0% wt magnesium ion carrier VI (ETH 5506), 0.8% wt potassium tetrakis(4-chlorophenyl)borate (KTpClPB), 67.3% wt 2-nitrophenyl octyl ether (o-NPOE), 15.45% wt polyvinyl chloride (PVC) and 15.45% wt polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene were mixed (a total of 100 mg), and then 1 mL of tetrahydrofuran (THF) was added and stirred at room temperature to obtain a transparent solution.

[0088] Preparation of all-solid-state ion selective electrode: 0.28 mg of CoS2-C / CNT-6h-500 was dripped on the surface of the pretreated glassy carbon electrode with a pipette and dried in a fume hood for later use. 100 μL of potassium ion selective membrane solution was dripped on the top of the above electrode in batches of 10 μL each time, and after dripping, it was placed in a fume hood to dry for 12 hours to obtain an all-solid-state potassium ion selective electrode based on CoS2-C / CNT-6h-500 as the transduction layer.

[0089] As above, the sodium, calcium and magnesium ion selective membrane solutions were drop-coated on the top of the above-mentioned electrodes respectively, and after drop-coating, they were placed in a fume hood to dry for 12 hours to obtain all-solid-state sodium, calcium and magnesium ion selective electrodes based on CoS2-C / CNT-6h-500 as the transduction layer.

[0090] Detection of potassium, sodium, calcium and magnesium ions:

[0091] The following is an example of the detection of potassium ions by an all-solid-state potassium ion selective electrode:

[0092] Before use, the all-solid-state potassium ion selective electrode was heated to 10 -3 M KCl solution for one day, and then - 9 The samples were activated in 100 M KCl solution for two days and the potential response test was performed using the open circuit potential test method. Fig. 9 In ab, the all-solid-state potassium ion selective electrode based on CoS2-C / CNT-6h-500 as the transduction layer was -2 -10 -5 The detection of potassium ions was achieved within the linear range of 10 -5.5 M, the Nernst slope is 57.10 mV / dec.

[0093] Similarly, the all-solid-state sodium ion selective electrode based on CoS2-C / CNT-6h-500 as the transduction layer has a high conductivity at a sodium ion concentration of 10 -2 -10 -5 The detection of sodium ions was achieved within the linear range of 10 -5.1 M, the Nernst slope is 58.84mV / dec (e.g. Fig. 9 (as shown in c and d);

[0094] The all-solid-state calcium ion selective electrode based on CoS2-C / CNT-6h-500 as the transduction layer has a high conductivity at a calcium ion concentration of 10 -1 -10 -7 The detection of calcium ions was achieved within the linear range of 10 -7.2 M, the Nernst slope is 27.58mV / dec (e.g. Fig. 9 (e and f in the figure);

[0095] The all-solid-state magnesium ion selective electrode based on CoS2-C / CNT-6h-500 as the transduction layer has a high magnesium ion concentration of 10 -1 -10 -6 The detection of magnesium ions was achieved within the linear range of 10 -6.3 M, the Nernst slope is 29.96mV / dec (e.g. Fig. 9(as shown in g and h).

[0096] Embodiment 2:

[0097] Preparation of CoS2-C / CNT composites:

[0098] S11. First, 30 mmol of cobalt sulfate heptahydrate (CoSO4·7H2O) was dissolved in 0.3 L of methanol to form solution 1; 60 mmol of 2-nitroimidazole was dissolved in 0.1 L of methanol to form solution 2.

[0099] S12. While stirring, slowly pour solution 1 into solution 2 and stir for 20 min, then let the mixture stand at 25°C for 36 h. After the stirring reaction, collect the purple precipitate by centrifugation and washing with methanol for 5 times, and vacuum dry at 60°C to obtain a ZIF-67 precursor.

[0100] S13, the ZIF-67 precursor powder was placed in a magnetic boat, and then placed in a tube furnace, and heated to 800°C at a heating rate of 2°C / min in a mixed atmosphere of argon and hydrogen (the volume content of hydrogen in the mixed gas was 5%), and calcined and carbonized for 6 hours. After cooling to room temperature, the carbide Co-C / CNT was collected.

[0101] S14, the carbide Co-C / CNT powder and sulfur powder are mixed and ground evenly at a mass ratio of 1:1, then put into a magnetic boat, and then placed in a tubular furnace, and calcine and sulfurize at 300°C at a heating rate of 2°C / min for 6 hours in a N2 atmosphere. After naturally cooling to room temperature, a CoS2-C / CNT composite material is obtained.

[0102] Embodiment 3:

[0103] Preparation of CoS2-C / CNT composites:

[0104] S11. First, 30 mmol of cobalt sulfate heptahydrate (CoSO4·7H2O) was dissolved in 0.3 L of methanol to form solution 1; 90 mmol of 2-nitroimidazole was dissolved in 0.1 L of methanol to form solution 2.

[0105] S12. While stirring, slowly pour solution 1 into solution 2 and stir for 40 min, then let the mixture stand at 20°C for 60 h. After the stirring reaction, collect the purple precipitate by centrifugation and washing with methanol for 5 times, and vacuum dry at 60°C to obtain a ZIF-67 precursor.

[0106] S13, the ZIF-67 precursor powder was placed in a magnetic boat, and then placed in a tube furnace, and heated to 700°C at a heating rate of 10°C / min in a N2 atmosphere, and calcined and carbonized for 8 hours. After cooling to room temperature, the carbide Co-C / CNT was collected.

[0107] S14, the carbide Co-C / CNT powder and sulfur powder are mixed and ground evenly at a mass ratio of 1:1.5, then put into a magnetic boat, and then placed in a tubular furnace, and calcine and sulfurize at 600°C for 4 hours at a heating rate of 10°C / min under an argon atmosphere. After naturally cooling to room temperature, a CoS2-C / CNT composite material is obtained.

[0108] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those familiar with the art can easily make various modifications to the implementation cases and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the implementation cases here, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An application of a CoS2-C / CNT composite material, characterized in that: The CoS2-C / CNT composite material is used as a transduction layer material in an all-solid-state ion selective electrode, and the all-solid-state ion selective electrode is used for detecting potassium, sodium, calcium or magnesium ions; The preparation method of the CoS2-C / CNT composite material comprises the following steps: S11, slowly pouring the cobalt salt solution into the organic ligand solution, stirring and reacting to obtain a ZIF-67 precursor; S12, calcining and carbonizing the ZIF-67 precursor in a carbonizing atmosphere to obtain carbide Co-C / CNT; the carbonizing atmosphere is a nitrogen atmosphere or a mixed atmosphere of argon and hydrogen, and the volume content of hydrogen in the mixed gas is 5%; the calcining and carbonizing is carried out at a heating rate of 2-10°C / min to 700-900°C, and calcining for 2-10h; S13. Grind and mix the carbide Co-C / CNT and sulfur powder, and then calcine and sulfurize them under nitrogen or argon to obtain a CoS2-C / CNT composite material; wherein the calcination and sulfurization are carried out by heating the temperature to 300-600°C at a heating rate of 2-10°C / min and calcining for 2-6h.

2. The use according to claim 1, characterized in that: The molar ratio of the cobalt salt to the organic ligand is 1:2-4; The cobalt salt is at least one of cobalt nitrate hexahydrate and cobalt sulfate heptahydrate; the organic ligand is at least one of 2-methylimidazole and 2-nitroimidazole.

3. The use according to claim 1, characterized in that: The stirring reaction in step S11 refers to stirring for 20-40 minutes first, and then standing at 20-25° C. for 36-60 hours; after the stirring reaction is completed, the product is centrifuged and washed with methanol, and vacuum dried to obtain the ZIF-67 precursor.

4. The use according to claim 1, characterized in that: In step S13, the mass ratio of carbide Co-C / CNT to sulfur powder is 1:1-1.

5.

5. The use according to claim 1, characterized in that: The preparation method of the all-solid-state ion selective electrode comprises the following steps: S21, ultrasonically dispersing the CoS2-C / CNT composite material in ethanol or deionized water to obtain a dispersion; S22, dripping the dispersion onto the electrode surface and drying; S23, drop-coating the ion selective membrane solution on the top of the electrode treated in step S22, and drying, thereby obtaining a fully solid-state ion selective electrode.

6. The use according to claim 5, characterized in that: The electrode is a glassy carbon electrode or a screen-printed electrode; The ion selective membrane solution is a potassium, sodium, calcium or magnesium ion membrane solution.

Citation Information

Patent Citations

  • Preparation and application of all-solid-state calcium ion selective electrode transduction layer electrode material

    CN112374549A